Technical change and total factor productivity growth: the case of Chinese provinces - Almas Heshmati; Subal C. Kumbhakar (Institute for the Study of Labor (IZA), 2010)
In the literature technical change is mostly assumed to be exogenous and specified as a function of time. However, some exogenous external factors other than time can also affect technical change. In this paper we model technical change via time trend (purely external non-economic) as well as other exogenous (external economic) factors (technology shifters). We define technology index based on the external economic factors which are indicators of 'technology'. Thus our definition of production function is amended to accommodate several technology shifters which are not separable from the traditional inputs. That is, these technology shifters allow for non-neutral shift in the production function. In doing so we are able to decompose technical change (a component of TFP change) into two parts. One part is driven by time (manna from heaven) and the other part is related to producer specific external economic factors. These exogenous technology shifters are aggregated (via hedonic aggregator functions) into several groups (technology indices) for parsimonious parametric specification. The empirical model uses panel data on Chinese provinces. We identify a number of key technology shifters and their effect on technical change and TFP growth of provinces.
Keywords: C33; C43; D24; O18; O47; 330; Technical change; total factor productivity growth; technology indicator; technology shifter; Chinese provinces; Technischer Fortschritt; Produktivität; Regionales Wachstum; Technologie; Zeitreihenanalyse; Schätzung; China